On a continued fraction of order twelve - Kahtan, Abdulrawf A. A.; Sathish, Kumar C.; Sharath, G.; Vasuki, K. R. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We present some new relations between a continued fraction U(q) of order twelve (which is established by M. S. M. Naika et al.) and U(q^n) for n = 7,9,11 and 13.